Transcriptomic responses provide a new mechanistic basis for the chemopreventive effects of folic acid and tributyrin in rat liver carcinogenesis. Issue 1 (22nd February 2014) - Guariento, Aline H.; Furtado, Kelly S.; de Conti, Aline; Campos, Adriana; Purgatto, Eduardo; Carrilho, Jéssica; Shinohara, Elvira Maria Guerra; Tryndyak, Volodymyr; Han, Tao; Fuscoe, James C.; Ross, Sharon A.; Beland, Frederick A.; et al.
Abstract : The steady increase in the incidence and mortality of hepatocellular carcinoma (HCC) signifies a crucial need to understand better its pathogenesis to improve clinical management and prevention of the disease. The aim of this study was to investigate molecular mechanisms for the chemopreventive effects of folic acid and tributyrin alone or in combination on rat hepatocarcinogenesis. Male Wistar rats were subjected to a classic "resistant hepatocyte" model of liver carcinogenesis and treated with folic acid and tributyrin alone or in combination for 5 weeks during promotion stage. Treatment with folic acid and tributyrin alone or in combination strongly inhibited the development of glutathione‐ S ‐transferase placental form (GSTP)‐positive foci. Microarray analysis showed significant changes in gene expression. A total of 498, 655 and 940 of differentially expressed genes, involved in cell cycle, p53‐signaling, angiogenesis and Wnt pathways, was identified in the livers of rats treated with folic acid, tributyrin or folic acid and tributyrin. A detailed analysis of these differentially expressed genes revealed that treatments inhibited angiogenesis in the preneoplastic livers. This was evidenced by the fact that 30 out of 77 differentially expressed genes common to all three treatments are involved in the regulation of the angiogenesis pathway. The inhibition of angiogenesis was confirmed by reduced levels of CD34 protein. In conclusion, the tumor‐suppressing activity of folic acid and tributyrin is associated with inhibition of angiogenesis at early stages of rat liver carcinogenesis. Importantly, the combination of folic acid and tributyrin has stronger chemopreventive effect than each of the compounds alone. Abstract : What's New? Active intervention with agents that suppress or attenuate early carcinogenesis or the progression of premalignant lesions represents a promising approach in cancer prevention. According to this study, for hepatocarcinogenesis, prevention may be effected through intervention with folic acid and tributyrin. The results demonstrate that the tumor‐suppressing activity of folic acid and tributyrin, along with inhibition of cell proliferation and activation of apoptosis, is associated with inhibition of angiogenesis in early stages of rat liver carcinogenesis. The findings emphasize a key role for angiogenesis in early hepatocarcinogenesis and indicate that angiogenesis is an imperative target for chemoprevention.